2004
DOI: 10.1093/glycob/cwh037
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion ordered spectroscopy as a complement to size exclusion chromatography in oligosaccharide analysis

Abstract: A series of N-acetyl-chitooligosaccharides (GlcNAc)(1-6) have been studied by a nuclear magnetic resonance (NMR) method, diffusion ordered spectroscopy (DOSY). DOSY has also been applied to two additional synthetic related oligosaccharides [GlcNH(2)-(GlcNAc)(4) and GlcNH(2)-(GlcNAc)(2)-GlcNAcSO(3)Na]. A plot of the log of the determined diffusion coefficients (logD) of (GlcNAc)(n) versus the log of molecular weight was linear (6 points, R(2) = 0.995). The molecular weights of the two synthetic chitin derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
2
63
0
1
Order By: Relevance
“…to provide MW information for samples being analyzed [32,[34][35][36][37][38][39]. Different forms of diffusion NMR experiments have been applied for diverse varieties of systems including inorganic materials [37,[40][41][42], organic molecules [17,23,24,28,[43][44][45][46][47][48][49] and polymers of different kinds (inorganic and organic polymers, polysaccharides, proteins) [21,37,[50][51][52][53][54][55][56][57][58][59][60][61][62]. Application for nucleic acids has been rather limited because the well-defined double helical structures have been investigated for most cases.…”
mentioning
confidence: 99%
“…to provide MW information for samples being analyzed [32,[34][35][36][37][38][39]. Different forms of diffusion NMR experiments have been applied for diverse varieties of systems including inorganic materials [37,[40][41][42], organic molecules [17,23,24,28,[43][44][45][46][47][48][49] and polymers of different kinds (inorganic and organic polymers, polysaccharides, proteins) [21,37,[50][51][52][53][54][55][56][57][58][59][60][61][62]. Application for nucleic acids has been rather limited because the well-defined double helical structures have been investigated for most cases.…”
mentioning
confidence: 99%
“…1-2 mm), the molecule behaved as a monomer, since at these concentrations the diffusion coefficient was basically identical to that previously reported for the chitin pentasaccharide. [11] Thus, the experimental data can be unambiguously correlated with a single species.…”
Section: Resultsmentioning
confidence: 94%
“…To properly evaluate the NOEs, and to discard the possibility of aggregates at the working concentration, NMR diffusion order spectroscopy (DOSY) experiments [11] were used to confirm the aggregation state of the molecules for the employed experimental conditions. It was confirmed that, at the working concentration (ca.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Among the NMR methods suitable for analyzing ligand binding, transferred NOE [12] and DOSY [13,14] are particularly useful for detection of binding based on changes in the rotational (TR-NOESY) and translational (DOSY) properties of the ligands upon binding to large receptors. These techniques are particularly useful in the medium-to-low affinity range, and, therefore it is speculated on whether they could be adopted to detect weak-affinity carbohydrate-carbohydrate interactions such as those described above.…”
Section: A C H T U N G T R E N N U N G Glcpnaca C H T U N G T R E N Nmentioning
confidence: 99%
“…Each measured log D value is a weighted average of the diffusion coefficients of receptorbound and free ligand. Therefore, ligands with NMR signals that show increases in apparent molecular weight signify a receptor-bound population, whereas ligands that do not bind to the receptor exhibit no change in log D. This approach has previously been used to characterize the binding of a small protein receptor (hevein) to different oligosaccharides, [13] to detect the binding of plant extracts to the lectin domain of cholera toxin, [14] and to characterize the interactions of organic ligands in suspensions of titanium dioxide nanoparticles. [15] In particular, pulsed field gradient NMR spectroscopy is an in situ methodology that enables the resolution of mixtures of different species in solution solely on the basis of their differentiated translational mobility.…”
Section: Dosy Experimentsmentioning
confidence: 99%